Teknik Interpretasi dalam Penafsiran - Hidayatullah (LP2M Universitas PTIQ Jakarta, 2018)
This paper discusses the techniques of interpretation in interpretation. In general the technique of interpretation can be divided into various types. First, textual interpretation techniques that refer to the meanings found in the Qur’an and al-Sunnah, sayings (qaul) of friends and tabiin. Second, linguistic interpretation techniques are traced through Arabic speech and dialect as the language of the Qur’an, both in talaqqi (face to face) and non-talaqqi (by way of learning linguistics and Arabic dictionaries). Third, the technique of systematic interpretation, which is done by determining a theme collected from the verses contained in the Qur’an. This method is known as the maudhu’i technique which is systemic and directed. Fourth, the technique of socio-historical interpretation, stressing techniques methodology in the historical detail revealed the Qur’an which relates to cultural, social, and historical language from revelations revealed to the Arabs as a social object.